Pyroptosis: A New Regulating Mechanism in Cardiovascular Disease - Ji N; Qi Z; Wang Y; Yang X; Yan Z; Li M; Ge Q; Zhang J (Dove Medical Press, 2021)
Nan Ji,1,2,* Zhongwen Qi,1,* Yueyao Wang,1 Xiaoya Yang,1 Zhipeng Yan,1 Meng Li,1 Qihui Ge,1 Junping Zhang1 1First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, 300183, People’s Republic of China; 2National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, Tianjin, 300193, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junping Zhang Email tjzhtcm@163.comAbstract: Pyroptosis is a kind of pro-inflammatory cell death. Compared with autophagy and apoptosis, pyroptosis has unique characteristics in morphology and mechanism. Specifically, pyroptosis is a kind of cell lysis mediated by the Gasdermin family, releases inflammatory cytokines IL-1β and IL-18. There are three different forms of mechanism, which are caspase-1-mediated, caspase-4/5/11-mediated and caspase-3-mediated. A large number of studies have proved that pyroptosis is closely related to cardiovascular disease. This paper reviewed the recent progress in the related research on pyroptosis and myocardial infarction, ischemia-reperfusion, atherosclerosis, diabetic cardiomyopathy, arrhythmia, heart failure hypertension and Kawasaki disease. Therefore, we believe that pyroptosis may be a new therapeutic target in the cardiovascular field.Keywords: pyroptosis, cardiopathy, NLRP3, caspase-1, IL-1β